"Green Technology" and Renewable Energy in the System of the Steel Industry in Europe - Dudin, Mihail Nikolaevich; Reshetov, Konstantin Yurievich; Mysachenko, Victor Ivanovich; Mironova, Natalia Nikolaevna; Divnenko, Olga Vladimirovna (International Journal of Energy Economics and Policy, 2017)
The purpose of this article is to review the potential applicability of the environmentally friendly metallurgical production technologies and potential replacement of traditional energy sources with renewable energy sources in this sector. The materials presented in this article lead to the following conclusions: i) the metallurgical production in Europe can be considered as one of the most important sectors forming a high added value. Simultaneously, the metallurgical production is characterized by relatively high energy consumption and generates a significant contribution to carbon dioxide emissions; ii) the metallurgical enterprises have to compete not only among themselves but also with other companies engaged in production of the substitute products (e.g. plastic pipes); therefore, the production and technological modernization and environmental optimization of the activity of the metallurgical enterprises in Europe is one of the ways to increase the competitiveness and to reduce the expense content; iii) the use of technologies that virtually eliminate the generation of carbon dioxide in the processing of iron ore allows to reduce the average level of greenhouse gas emissions by an average of 20-25%; iv) the integration of production technology characterized by very low CO2 emissions with the use of solar thermal energy technologies to provide the energy needs of the metallurgical production can significantly reduce the level of energy consumption of the metallurgical plants by an average of 18-31%. Keywords: metallurgy, renewable energy, green technology, the greening of production, Europe. JEL Classifications: O10, Q40, Q42, Q43